Foundational Aspects of Family-School Partnership Research - Sheridan, Susan M (Springer, 2016)
This volume focuses on how family-school partnerships are conceptualized, defined, and operationalized as well as the research that is needed to advance these foundational issues. Each chapter integrates prevailing approaches into a research-based framework for supporting learning from pre-K through high school. The book incorporates structural and relational methods into the larger context of educational processes to promote research about collaboration and to improve the academic and behavioral development of students. Diverse theories and models of family-school alliances demonstrate approaches and interventions that are goal-directed and strengths-based, respectful and responsive. In addition, the book analyzes cognitive, behavioral, and interpersonal aspects of partnership and discusses different methods of assessing parental involvement and student outcomes.